2020
DOI: 10.1155/2020/3543568
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Effectiveness of Real‐World Administration of Concomitant Viscum album L. Therapy for the Treatment of Stage IV Pancreatic Cancer

Abstract: Background. For patients receiving add-on Viscum album L. (VA) treatments for late-stage pancreatic cancer, an improved overall survival (OS) was observed. Only limited information regarding cost-effectiveness (CE) for comparisons between standard of care and standard of care plus add-on VA in stage IV pancreatic cancer treatment is available. The present study assessed the costs and cost-effectiveness of standard of care plus VA (V) compared to standard of care alone (C) for a hospital in Germany. Methods. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…However, for the treatment regimen, it might be difficult to select a sample in a real-world setting where the treatment regimen is always complicated ( Schulman et al, 2013 ). Consequently, those studies aiming to compare different treatment regimens preferred to use a model approach that allows greater freedom in the choice of study and control groups ( Behar et al, 2017 ; Thronicke et al, 2020 ). This might be due to the fact that most of the studies with the model used sensitivity analysis to control for uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…However, for the treatment regimen, it might be difficult to select a sample in a real-world setting where the treatment regimen is always complicated ( Schulman et al, 2013 ). Consequently, those studies aiming to compare different treatment regimens preferred to use a model approach that allows greater freedom in the choice of study and control groups ( Behar et al, 2017 ; Thronicke et al, 2020 ). This might be due to the fact that most of the studies with the model used sensitivity analysis to control for uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…The 36 cohort studies can be divided into controlled and non-controlled studies. Of these, 29 studies (16 publications respectively) are designed as controlled studies (Augustin et al 2005 ; Bock et al 2004a , 2014 ; Beuth et al 2008 ; Friedel et al 2009 ; Grossarth-Maticek and Ziegler 2006a , b , 2007a , b , 2007 c, 2008 ; Matthes et al 2010 ; Schumacher et al 2003 ; Thronicke et al 2017 , 2020a ; Zaenker et al 2012 ) Of the studies published by Grossarth-Maticek, eight were randomized matched-pair studies, and eleven were non-randomized matched-pair studies. The remaining cohort studies are non-controlled (Brandenberger et al 2012 ; Oei et al 2019a , b ; Schad et al 2017 , 2018a , b ; Thronicke et al 2020b ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, a current systematic review on the clinical efficacy of VA therapy indicates a significant improvement of survival for patients with lung cancer receiving VA therapy [27]. This evidence is supported by results from a multicentre RWD study revealing that the combination of chemotherapy and VA therapy significantly prolonged overall survival of stage IV non-small cell lung cancer patients and even at similar costs compared to chemotherapy alone [28, 29]. It is considered by the authors of this review that these results should be considered in new editions of current guidelines or in new guidelines, especially in the palliative field.…”
Section: Add-on Va Extracts For Patients With Lung Cancermentioning
confidence: 95%
“…In addition, another multicentre RWD study of patients with pancreatic cancer showed prolonged survival rates, an improved HRQL, and a reduction in side effects of standard oncological treatment in the VA group [41]. The results of a first-ever published RWD cost-effectiveness study for patients with stage IV pancreatic cancer revealed that chemotherapy plus VA therapy was equally cost-effective compared to chemotherapy alone [29].…”
Section: Add-on Va Extracts For Patients With Gastric Colorectal and ...mentioning
confidence: 99%